Necrotizing enterocolitis, sepsis, and diarrhea due to cow's milk allergy in a full-term infant with Hypothyroidism: a case report - Arumndari, Runi; Putri, Asterisa Retno; Liman, Claudia Natasha; Suryaningsih, Putu Siska (Pediatric Sciences Journal, 2023)
Introduction: Necrotizing enterocolitis (NEC) remains one of neonates' most common gastrointestinal diseases. NEC is allegedly to be a multifactorial disease. Some of the predisposing factors are cow’s milk formula (CMF) feeding or not being breast-fed from birth, sepsis, and Hypothyroidism. Case: An 8-day-old full-term baby girl was admitted with an initial diagnosis of sepsis and acute diarrhea due to cow's milk allergy. She had never been breast-fed from birth. She also had a fever, signs of mild-to-moderate dehydration, a C-Reactive Protein (CRP) level at 114, leukocyte 6.280/ul, platelet counts 477.000/ul, and fat on the stool test. She was given Cefotaxime, probiotics, zinc, and a hypoallergenic milk formula. Her condition worsened on the 4th day of hospitalization. She showed abdominal distention, bradypnea, and vomiting. She was then fasting, required a nasal cannula oxygen, and undergone several laboratory examinations showing leukocyte 4.980/ul, platelet count 54.300/ul, and a positive fecal occult blood test. An abdominal x-ray showed an increased bowel gas. She was then diagnosed with grade I NEC, and the antibiotic was changed to Meropenem, added with Metronidazole. She also undergone a thyroid hormone screening, had a TSH level of 6.36 and FT4 1.23, and thus was given Levothyroxine. Her condition improved gradually. After being given Meropenem for 7 days, she was discharged on the 12th day of hospitalization in good condition. Two days later, during the clinic’s follow-up, she was in good health, and it was planned that she would do a follow-up examination for thyroid hormones a month later. Conclusion: Cow’s milk allergy can be severe enough to develop sepsis. Meanwhile, both are predisposing factors for NEC. Hypothyroidism can also be a predisposing factor by causing a decrease in intestinal motility, which plays a role in bacterial overgrowth. A study in animals showed that bacteria play an important role in the development of NEC because NEC will not occur in a germ-free environment but can only develop after exposure to microbes. Conservative treatment for NEC includes broad-spectrum antibiotics, bowel rest, and abdominal decompression.